2013
DOI: 10.1177/0960327112467042
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic cell death in rat epididymis following epichlorohydrin treatment

Abstract: Epichlorohydrin (ECH) is an antifertility agent that acts both as an epididymal toxicant and an agent capable of directly affecting sperm motility. This study identified the time course of apoptotic cell death in rat epididymides after ECH treatment. Rats were administrated with a single oral dose of ECH (50 mg/kg). ECH-induced apoptotic changes were evaluated by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay and its related mechanism was confirmed by Western blot analysis and color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…The mitogen‐activated protein kinases (MAPKs), as the serine/threonine protein kinases, are activated by different extracellular stimuli, such as cytokines, neurotransmitters, hormones, cell stress, and cell adhesion . The activated MAPKs can phosphorylate the nuclear transcription factor, then regulate the transcription of related genes, participating in tissue fibrosis . For mammals, members of the MAPKs superfamily mainly include the ERK, p38 MAPK, and c‐JUN, NH2‐terminal protein kinase (JNK) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitogen‐activated protein kinases (MAPKs), as the serine/threonine protein kinases, are activated by different extracellular stimuli, such as cytokines, neurotransmitters, hormones, cell stress, and cell adhesion . The activated MAPKs can phosphorylate the nuclear transcription factor, then regulate the transcription of related genes, participating in tissue fibrosis . For mammals, members of the MAPKs superfamily mainly include the ERK, p38 MAPK, and c‐JUN, NH2‐terminal protein kinase (JNK) .…”
Section: Introductionmentioning
confidence: 99%
“…17 The activated MAPKs can phosphorylate the nuclear transcription factor, then regulate the transcription of related genes, participating in tissue fibrosis. 18 For mammals, members of the MAPKs superfamily mainly include the ERK, p38 MAPK, and c-JUN, NH2-terminal protein kinase (JNK). 19 Although study has shown that MAPK signaling pathway could be activated in the signal transduction of the TGF-β1-induced pulmonary fibrosis, 16 it still have differences between species and cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, different models of facilities were compared and selected. Previous studies also suggested that students’ independent inquiry around problems and reconstruction of knowledge would greatly contribute to cognition development and engineering practical ability. …”
Section: Results and Discussionmentioning
confidence: 99%
“…Epichlorohydrin vapors are strongly irritating to the respiratory tract; inhalation at high concentrations causes central nervous system depression and can be fatal . Repeated and prolonged inhalation can cause lung, liver, and kidney injuries and even cause cancer . Direct skin or eyes contact with liquids may cause burns.…”
Section: Hazardsmentioning
confidence: 99%
“…Apoptosis is also known to be correlated with autoimmune diseases such as rheumatic arthritis [ 23 24 ], atherosclerosis, and cardiomyopathy. In particular, a study reported an increase in caspase-3 expression in epididymal tubules after the injection of epichlorohydrin—an antifertility agent that is directly toxic to the epididymis and inhibits sperm motility [ 25 ]. The expression of caspase-3 in the epididymal tubules of C57BL/6N mice, detected in the present study, was not observed in ICR or BALB/c nude mice or SD rats, which implies that it is characteristic to C57BL/6N mice.…”
Section: Discussionmentioning
confidence: 99%